A taxonomic guide to the brittle-stars (Echinodermata, Ophiuroidea) from the State of Paraíba continental shelf, Northeastern Brazil - Gondim, Anne I. (Pensoft Publishers, 2013)
Abstract. We provide the first annotated checklist of ophiuroids from the continental shelf of the State of Paraíba, northeastern Brazil. Identification keys and taxonomic diagnoses for 23 species, belonging to 14 genera and 8 families, are provided. The material is deposited in the Invertebrate Collection Paulo Young, at the Federal University of Paraíba. Ophiopsila hartmeyeri represents the first record for the northeastern region of Brazil, while Ophiolepis impressa, Ophiolepis paucispina, Amphiura stimpsoni, Amphiodia riisei, Ophiactis quinqueradia, Ophiocoma wendtii and Ophionereis olivaceae are new records for the State of Paraíba. The number of species known for the state was increased from 16 to 23, representing approximately 17% of the species known for Brazil and 54% of the species known for northeastern Brazil. The recorded fauna has a large geographical and bathymetrical distribution.